Revitalisasi Mitos Gunung Siklop (Cyclop): Sebuah Alternatif Konservasi Danau Sentani - Sri Yono Sri Yono (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Sentani  Lake as an icon of Jayapura has an important role both economically and ecologically. Unfortunately, this lake has been polluted and becoming shallow due to sedimentation. The water quality of this lake getting worse and worse from time to time. Domestic garbage spreads on the side of this lake. It seems that Sentani Lake has changed to be a giant garbage dam. One major factor causing this condition is the deforest of cycloop mountain. As an upstream and resource of water, Cycloop mountain should be protected from the destruction. This paper tries to offer a new way of threatening environment through revitalization of myth. As a product of oral tradition, we could learn about the identity, way of life, belief, value, and culture of such a community from myth.